A matter of honor - Archer, Jeffery . (Pocket Books, 1987)
When Colonel Scott dies, his will points the way to clearing the unspoken secret that shadowed his retirement and turned him from a World War II hero into a disgraced and broken man. It is up to his son, Adam, to follow. The path leads to a Swiss bank and a vault, strongly guarded. It contains a priceless Russian icon, smuggled out of Russia by the last Czar, before passing into the hands of a Nazi war criminal. As Adam works to clear his father's name, he stumbles across a revelation so explosive, so charged, so unexpected that it could change the balance of power between America and the Soviet Union. Suddenly, Adam is in great danger